Spatial analysis on the impact of Islamic regional financial depth on income inequality in Indonesia - Prastowo Prastowo; Diyah Putriani (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This paper aims to analyze the effect of financial depth in Islamic banks on income inequality in 33 provinces in Indonesia. Methodology – We use data for the period 2010-2018 from 33 provinces in Indonesia which are estimated using panel data to develop spatial panel data model. The dependent variable is income inequality, while the variable independent are Islamic regional financial depth, economic growth, human capital, and government expenditure.Findings – This research finds that Islamic Regional Financial Depth (FDS) has a positive and statistically significant direct effect on income inequality represented by Gini index. It means that an increase in the FDS will also cause an increase in the level of Gini index. In addition, the indirect effect of FDS on income inequality is also positive and significant, indicating that the ratio of financing to GRDP has a spillover effect on connected regions. Implications – This research recommends policymaker to expand the business of Islamic banking by financing the small medium enterprises and concern on the promotion of Islamic banking in the regional level. Originality – This study is potentially to contribute and be the early work which employs spatial analysis in the area of Islamic economics and finance. In addition, this study examines the impact of financial depth in Islamic bank on income inequality which is rarely discussed. Hence, this study presents relatively new information for policy makers, practitioners and researchers.